Vers une modernisation énergétique : territorialisation conflictuelle et gouvernement de la critique des nouvelles infrastructures énergétiques en moyenne montagne - Jimmy Grimault (Revue de Géographie Alpine)
This paper sets out to study the changes underway, dubbed “ecological transition”, through the prism of “ecological modernisation”, which involves fitting the environment into the capitalist mindset without making any fundamental changes in this regard. It explores conflictual territorialisation and the government of criticism of new energy infrastructure in mid-mountain regions. Mid-mountain areas appear to be ambivalent where energy infrastructure is concerned. They are both drawn to wind farms (economic and symbolic benefits) and partially incompatible (challenges in terms of the environment and landscape which can spark conflicts of use). Their territorialisation is therefore subject to regulation, negotiation and resistance. Opponents to infrastructure which symbolises ecology for the sake of ecology are picking back up the gauntlet of environmental protest and proposing new, competing technological trajectories (Fressoz, 2012). To ensure the smooth deployment of energy infrastructure, eco-modernisers therefore need to rethink their acceptability strategies (Oiry, 2017). In such a context, mid-mountain regions come across as testing grounds for the government of criticism (Topçu, 2013): new schemes are being tested in them, including local investment and door-to-door. These schemes do not nip all forms of resistance in the bud, however, far from it.